1996
DOI: 10.1002/chem.19960020117
|View full text |Cite
|
Sign up to set email alerts
|

Bimetallic Sesquifulvalene Complexes–Compounds with Unusually Large Hyperpolarizability β

Abstract: Abstract:In order to construct bimetallic organometallic donor-acceptor complexes with nonlinear optical (NLO) properties, the bimetallic sesquifulvalene com-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
49
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 95 publications
(55 citation statements)
references
References 32 publications
(1 reference statement)
6
49
0
Order By: Relevance
“…This might have a significant bearing for areas such as catalysis [1][2][3][4][5][6], molecular electronics [7][8][9][10][11][12], nonlinear optics [13,14] and electron transfer chemistry [15]. Among the complexes without direct metal-metal bonds in particular those with connecting p systems are promising candidates for electronic interactions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This might have a significant bearing for areas such as catalysis [1][2][3][4][5][6], molecular electronics [7][8][9][10][11][12], nonlinear optics [13,14] and electron transfer chemistry [15]. Among the complexes without direct metal-metal bonds in particular those with connecting p systems are promising candidates for electronic interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Such interactions might result in new properties deriving from either participating metal and might therefore be different from a formal sum of the distinct properties caused by the single metal. In many cases, metals of oligonuclear complexes are connected by p ligands such as fulvalenes [7,14,[16][17][18][19], biphenyl [7,[20][21][22][23][24][25], stilbene [26], oligophenylenes [27], etc. Alternatively there are complexes, in which the metals are directly incorporated in the connecting p system, for example in bimetallic cumulenylidene or oligoalkynediyl complexes [28][29][30][31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…[1,2] As in DϪA substituted polyenes, a description of the bonding situation in mono-and dinuclear sesquifulvalene complexes which demonstrates weak to strong NLO effects, is achieved by different mesomeric forms. [3,4] It would be worthwhile to know, whether a contribution of the cross-conjugated form B to the ground state would affect the SHG according to the BLA in acyclic α,ω-donorϪacceptor substituted conjugated polyenes. [3,4] It would be worthwhile to know, whether a contribution of the cross-conjugated form B to the ground state would affect the SHG according to the BLA in acyclic α,ω-donorϪacceptor substituted conjugated polyenes.…”
Section: Introductionmentioning
confidence: 99%
“…For dyes [11][12][13] The LB f'dms of 14--16 have Z-type structure, and their SHG values are high. It was found that long-chain homologs do not invert during deposition; the molecules adopt a stretched rather than a U-shaped configuration at the air-water interface.…”
Section: Imentioning
confidence: 99%